Islamic Religious Education and Practical Theology: Disciplinary Profiles and Key Research Areas in the German-Speaking Context - Ulfat, Fahimah (International journal of practical theology, 2025)
This article provides a systematic overview of the disciplinary profiles and key research areas of Islamic Religious Education (IRE) and Islamic Practical Theology (IPT) in the German-speaking context. Their development is closely linked to migration and education policy processes; in particular, IRE, as the first Islamic-theological discipline at German universities, played a pioneering role in the institutional establishment of Islamic theology. While IRE has since established itself as an independent discipline with both theological and pedagogical foundations, IPT is still in an early phase of profile and structural development.